PROCESS FOR THE DESIGN AND CONSTRUCTION OF A NETWORK OF EDUCATING CITIES IN VALLE DEL CAUCA - REDCIUDE ¿HOW TO DEVELOP THE FUTURE Of REDCIUDE? - Betancourt, Benjamín (Cuadernos de Administración, 2008)
The main objective of this artic1e is to describe the foresight methodological process and strategic that was developed for the design and implementation in the Valle del Cauca (Colombia) of a network of Educating Cities (RedCiudE) to serve as a platform for skills training of endogenous capabilities of human talent, in life sciences and innovation for Jocal development. The axes for structuring the design ofthe network are constituted for the size of city that allow to set up a new model ofhuman development, b::tst:d on Education, Knowledge and Development. The thematic elements that feed the model RedCiudE are as follows: Economic Dimension Dimension Socio-Cultural Management of Public Policy City, Social Knowledge Managemcnt [C1'5 (lnformation Technologies and Communication), Physical Environmental Management , Human Talent Training  and Thought F oresight. The methodology is an exercise in participative planning into four phases: Foresight, strategic, operational and Socialization, which are pres-:nt the social actors ofthe city. The first phase - Foresight - seeks to consolidate the program of the Agenda for Science Technology and Innovation, identifying scenarios for the fu tu re of Educating City, then specify the betting of each city and finally build the model of Educating Cities Network. The second phase - Strategic - proposes a comprehensive and holistic manner, a broad portfolio of projects and long-term plans for the different dimensions of city, aimed at strengthening education, knowledge and development, incorporating them into Development Plans ofthe respective towns with the purpose of compromising the support of local governments to achieve a better Jife quaJity for its citizens and communities in a sustainable manner over the long termo In keeping with the aboye raises the operational phase with the urgent need to start run plans under the guidance of local governments, in search of important strategies selected for Educating City and the tasks and subtasks of programs and strategic projects from RedCiudE, as well as its timetable for implementation, the allocation of responsibilities, resources and budget, and the design of a system for monitoring and control with management indicators for its realization. Then becomes the model of the Network for its operation (By way of rnode/ing  phase). Final1y,with the phase ofSociaJization is seeking to make known the results achieved through forums, pamphlets, seminars and the media. It also intends to immediately put these results into consideration of all the institutions involved in the process, in order to encourage the dialogue of city and between cities, which will be most valuable and strategic inasmuch to grow the network in the regional level, with greater participation and commitment of the social and institutional actors of all towns in the Valle del Cauca. making more efficient and effective the network.